2005
DOI: 10.1161/01.atv.0000182904.08513.60
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Soluble CD40 Ligand, Atherosclerosis Risk Factors, and Subclinical Atherosclerosis

Abstract: Objectives-The purpose of this study was to evaluate the associations between plasma levels of soluble CD40 ligand (sCD40L), atherosclerosis risk factors, and evidence of subclinical atherosclerosis. Methods and Results-Plasma levels of sCD40L were measured in 2811 subjects from the Dallas Heart Study, a multiethnic population-based cross-sectional study. Electron Beam Computed Tomography measurements of coronary artery calcium (CAC) and MRI measurements of aortic plaque were performed in 2198 and 1965 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 44 publications
6
56
1
Order By: Relevance
“…We also found a statistically significant inverse relation between smoking status and plasma CD40L, unlike others. 21 Potential explanations for the contrast between our findings with respect to serum and plasma CD40L compared with others may be due to differences in biomarker collection techniques, study sample, covariate adjustment, and smoking status definitions. We are uncertain why plasma CD40L concentrations were higher in never smokers, and smokers with the fewest pack-years exposure, in contrast to the lack of a trend with serum CD40L.…”
Section: Individual Markerscontrasting
confidence: 81%
See 1 more Smart Citation
“…We also found a statistically significant inverse relation between smoking status and plasma CD40L, unlike others. 21 Potential explanations for the contrast between our findings with respect to serum and plasma CD40L compared with others may be due to differences in biomarker collection techniques, study sample, covariate adjustment, and smoking status definitions. We are uncertain why plasma CD40L concentrations were higher in never smokers, and smokers with the fewest pack-years exposure, in contrast to the lack of a trend with serum CD40L.…”
Section: Individual Markerscontrasting
confidence: 81%
“…15,19 MCP-1, a chemokine found in atherosclerotic plaque, attracts monocytes to developing plaque. 21,22 MPO, a leukocyte enzyme, is elevated in culprit lesions of patients with acute coronary syndrome. 20 Urinary isoprostanes indexed to urinary creatinine (isoprostanes) are measures of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…One prospective study (21) showed that apparently healthy women with elevation of baseline sCD40L will have higher future cardiovascular event rate. However, de Lemos et al (22) reported sCD40L was not associated with subclinical atherosclerosis, as evaluated by the coronary calcium score of the electron beam computed tomography examination in a population-based study. Moreover, Verma et al (23) reported poor correlation between sCD40L and the calculated Framingham CAD risk score in a healthy, middle-aged male cohort.…”
Section: Discussionmentioning
confidence: 91%
“…† Significantly different from the low-sCD40L group, P , 0.05. mentioned by us, 5 none of these studies exclusively assessed STEMI patients or variations of sCD40L over time as in the current work. Furthermore, more recent studies not only fail to demonstrate an association of high level of sCD40L with increased risk of cardiovascular events, [21][22][23][24] but in fact, indicate an inverse relation of sCD40L levels with risk of recurrent ischemia. 23 The CD40/CD40L system represents a major costimulator system triggering different signaling pathways mainly attending as amplification of immune and inflammatory responses, 25 including in endothelial cells.…”
Section: Discussionmentioning
confidence: 98%